2021
DOI: 10.1016/j.jhep.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ADAPT, FIB-4 and APRI as non-invasive predictors of liver fibrosis and NASH within the CENTAUR screening population

Abstract: Background & Aims: The development of accurate non-invasive tests to detect and measure the extent of fibrosis and disease activity in patients with non-alcoholic steatohepatitis (NASH)the progressive phenotype of non-alcoholic fatty liver disease (NAFLD) is of great clinical importance. Herein, we aimed to validate the performance of PRO-C3 and ADAPT for the detection of moderate/ severe fibrosis within the CENTAUR screening population. Methods: PRO-C3 was assessed in plasma from the screening population of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…The study flow diagram is shown in Figure 1 . Seven of the included studies were full text reports [ 28 , 29 , 30 , 41 , 43 , 44 , 45 ] and one was an abstract [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study flow diagram is shown in Figure 1 . Seven of the included studies were full text reports [ 28 , 29 , 30 , 41 , 43 , 44 , 45 ] and one was an abstract [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven out of the eight studies were designed as diagnostic accuracy studies, while one was an exercise intervention trial that reported Pro-C3 values and liver biopsies at baseline [ 44 ]. Included patients were mostly from Western countries (United States and Europe); two studies also included participants from Asia and Australia [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations